PENGETAHUAN TANAMAN OBAT TRADISIONAL UNTUK PENYAKIT ANAK PADA KOMUNITAS REMAJA DI BALI : SEBUAH KAJIAN EKOLINGUISTIK - I Wayan Rasna (Bumi Lestari Journal of Environment, 2013)
AbstractThis study aims at knowing: 1) the level of young generations’ knowledge about the use oftraditional medical plantation for curing children’s diseases; and 2) the implication of theaims 1 above to Eco linguistics. This study took place in the province of Bali, consisting of8 regencies and one city government. The total samples of the study were 225 younggenerations’ and 45 spiritual people. The samples of the study were determined by usingpurposive quota sampling. The data related to the young generations’ knowledge werecollected through test. The data as to the implication of aims 1 were gathered by means ofinterview. The result of the study shows that: 1) the Balinese young generations’ knowledgeabout the use of traditional medical plantation is 48.4% (not enough); and 2) the younggenerations having better knowledge and will be more familiar with the terms of medicalplantation, such as the young generations in Karangasem with the percentage of 73.12%(good), the young generations in Klungkung 70.50% (good), and Bangli 71.36% (good).They are a bit more familiar with medical plantation terms. Referring to the result of thestudy, it is suggested to socialize about the usefulness of medical plantation, the improvementof the skill in producing medicine from medical plantation, and synergizing the relatedcomponents to lexical maintenance and environment.